Persepsi Relationship Marketing, Komitmen Pelanggan dan Loyalitas Pelanggan: Kajian dalam Pemasaran Retail - Dwi Irawati (SEGMEN Jurnal Manajemen dan Bisnis, 2006)
Creating customer loyalty is an effort, which has to be developed and maintained by an organization doing marketing activities. This is considered important because, by doing so, it will lead the organization remain survives and develop its competitive advantage. This research article suggests how the customers perception influences the activities of relationship marketing (RM), conducted by the organization toward the customers’ loyalty and commitment.  There is a positive influence of the customer commitment toward customer loyalty. Keywords:  customer loyalty, relationship marketing, customer commitment